A combined solar and geomagnetic index for thermospheric climate. Issue 10 (23rd May 2015) - Mlynczak, Martin G.; Hunt, Linda A.; Marshall, B. Thomas; Russell, James M.; Mertens, Christopher J.; Thompson, R. Earl; Gordley, Larry L.
Abstract Infrared radiation from nitric oxide (NO) at 5.3 µm is a primary mechanism by which the thermosphere cools to space. The Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument on the NASA Thermosphere‐Ionosphere‐Mesosphere Energetics and Dynamics satellite has been measuring thermospheric cooling by NO for over 13 years. In this letter we show that the SABER time series of globally integrated infrared power (watts) radiated by NO can be replicated accurately by a multiple linear regression fit using the F10.7, Ap, and Dst indices. This allows reconstruction of the NO power time series back nearly 70 years with extant databases of these indices. The relative roles of solar ultraviolet and geomagnetic processes in determining the NO cooling are derived and shown to vary significantly over the solar cycle. The NO power is a fundamental integral constraint on the thermospheric climate, and the time series presented here can be used to test upper atmosphere models over seven different solar cycles.